2018
DOI: 10.3390/microorganisms6030075
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila in the Human Gastrointestinal Tract: When, Where, and How?

Abstract: Akkermansia muciniphila is a mucin-degrading bacterium of the phylum Verrucomicrobia. Its abundance in the human intestinal tract is inversely correlated to several disease states. A. muciniphila resides in the mucus layer of the large intestine, where it is involved in maintaining intestinal integrity. We explore the presence of Akkermansia-like spp. based on its 16S rRNA sequence and metagenomic signatures in the human body so as to understand its colonization pattern in time and space. A. muciniphila signat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
259
3
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 321 publications
(284 citation statements)
references
References 189 publications
(319 reference statements)
11
259
3
11
Order By: Relevance
“…Various studies have described positive associations between the abundance of Akkermansia and intestinal health [3, 4]. For example, A. muciniphila affects glucose metabolism, intestinal immunity, and its abundance in the gastrointestinal tract (GIT) is inversely correlated with diseases including Crohn’s disease, ulcerative colitis, and acute appendicitis [3235]. Although a number of 16S rRNA gene variants have been observed [12] and dozens of isolates have been obtained [14], human-associated Akkermansia have largely been thought of as a single species and the functional potential beyond mucin degradation has gone largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various studies have described positive associations between the abundance of Akkermansia and intestinal health [3, 4]. For example, A. muciniphila affects glucose metabolism, intestinal immunity, and its abundance in the gastrointestinal tract (GIT) is inversely correlated with diseases including Crohn’s disease, ulcerative colitis, and acute appendicitis [3235]. Although a number of 16S rRNA gene variants have been observed [12] and dozens of isolates have been obtained [14], human-associated Akkermansia have largely been thought of as a single species and the functional potential beyond mucin degradation has gone largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Through comparative genomic analysis, we identified four phylogroups of human-associated Akkermansia , expanding the known genomic diversity of this lineage. Although all 16S rRNA gene sequenced examined here and elsewhere [32] are >97% identical, using an ANI of 95% across genomes as a species level delineation [36, 37] would suggest that each phylogroup represents a different species of Akkermansia . When we examined gene content, several phylogroup specific genes were identified that are predicted to code for functional differences amongst phylogroups further supporting species delineation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A. muciniphila is a mucin degrader most abundantly present in the colon able to colonize the mucus layer of the human intestinal tract and reported to play an important role in maintaining the gut barrier . A. muciniphila is capable of using mucin as a carbon, nitrogen, and energy source, and releasing sulfate in a free form .…”
Section: Introductionmentioning
confidence: 99%